Kepemimpinan Presiden Donald Trump terhadap Keamanan Perbatasan Amerika Serikat dan Meksiko: Studi Kasus Trump Wall (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This article was written with the aim of analyzing the idiosyncratic Donald Trump who issued the policy of building the Trump Wall on the border between the United States and Mexico with the aim of addressing the increase in illegal immigrants and improving border security. On the U.S.-Mexico border, crime is at a very complex level because it is difficult to detect by the security forces of the two countries, especially the problem of illegal immigrants, even the level of difficulty increases as a result of some border guards choosing to help these crimes occur. Therefore, this article uses a qualitative descriptive method by conducting library research for the purpose of collecting the data needed to understand the influence of Donald Trump's leadership on the Trump Wall policy applied to the United States border with Mexico. Trump's personal background, including his father's assertive influence and his military academy education that Trump had felt, shaped the character of his harsh and aggressive approach to border security. Politically, Trump has tapped into a populist-conservative philosophy aligned with anti-immigrant groups in the Republican Party, using rhetoric that often attacks immigrant groups, which has significantly increased in percentage from previous presidents.